Negatieve exponent (reeks 2)

Hoofdmenu Eentje per keer 

Zet om naar een positieve exponent

  1. \(\left(\frac{-18}{7}\right)^{-3}\)
  2. \(-\left(\frac{-2}{5}\right)^{-1}\)
  3. \(-\left(\frac{-11}{6}\right)^{-1}\)
  4. \(\left(\frac{-5}{2}\right)^{-4}\)
  5. \(-\left(\frac{-5}{7}\right)^{-1}\)
  6. \(\left(\frac{-11}{4}\right)^{-3}\)
  7. \(-\left(\frac{-20}{3}\right)^{-2}\)
  8. \(-\left(\frac{-8}{7}\right)^{-1}\)
  9. \(-\left(\frac{-5}{6}\right)^{-1}\)
  10. \(\left(\frac{-19}{6}\right)^{-4}\)
  11. \(\left(\frac{-3}{7}\right)^{-4}\)
  12. \(\left(\frac{-13}{3}\right)^{-3}\)

Zet om naar een positieve exponent

Verbetersleutel

  1. \(\left(\frac{-18}{7}\right)^{-3}=\left(-\frac{7}{18}\right)^{3}=- \frac{7^{3}}{18^{3}}=\ldots \text{ZRM}\)
  2. \(-\left(\frac{-2}{5}\right)^{-1}=-\left(-\frac{5}{2}\right)^{1}= \frac{5^{1}}{2^{1}}= \frac{5}{2}\)
  3. \(-\left(\frac{-11}{6}\right)^{-1}=-\left(-\frac{6}{11}\right)^{1}= \frac{6^{1}}{11^{1}}= \frac{6}{11}\)
  4. \(\left(\frac{-5}{2}\right)^{-4}=\left(-\frac{2}{5}\right)^{4}= \frac{2^{4}}{5^{4}}=\ldots \text{ZRM}\)
  5. \(-\left(\frac{-5}{7}\right)^{-1}=-\left(-\frac{7}{5}\right)^{1}= \frac{7^{1}}{5^{1}}= \frac{7}{5}\)
  6. \(\left(\frac{-11}{4}\right)^{-3}=\left(-\frac{4}{11}\right)^{3}=- \frac{4^{3}}{11^{3}}=\ldots \text{ZRM}\)
  7. \(-\left(\frac{-20}{3}\right)^{-2}=-\left(-\frac{3}{20}\right)^{2}=- \frac{3^{2}}{20^{2}}=- \frac{9}{400}\)
  8. \(-\left(\frac{-8}{7}\right)^{-1}=-\left(-\frac{7}{8}\right)^{1}= \frac{7^{1}}{8^{1}}= \frac{7}{8}\)
  9. \(-\left(\frac{-5}{6}\right)^{-1}=-\left(-\frac{6}{5}\right)^{1}= \frac{6^{1}}{5^{1}}= \frac{6}{5}\)
  10. \(\left(\frac{-19}{6}\right)^{-4}=\left(-\frac{6}{19}\right)^{4}= \frac{6^{4}}{19^{4}}=\ldots \text{ZRM}\)
  11. \(\left(\frac{-3}{7}\right)^{-4}=\left(-\frac{7}{3}\right)^{4}= \frac{7^{4}}{3^{4}}=\ldots \text{ZRM}\)
  12. \(\left(\frac{-13}{3}\right)^{-3}=\left(-\frac{3}{13}\right)^{3}=- \frac{3^{3}}{13^{3}}=\ldots \text{ZRM}\)
Oefeningengenerator vanhoeckes.be/wiskunde 2022-06-27 06:51:59